Developing a recovery-oriented intervention for people with severe mental illness and an intellectual disability: design-oriented action research - Berger, Ingeborg; Bruineberg, Anne; van Ewijk, Margot; de Jong, Levi; van der Hout, Michiel; van Weeghel, Jaap; van der Meer, Lisette (Frontiers in Psychiatry, 2023)
Mild intellectual disability or borderline intellectual functioning (MID/BIF) are common in people with severe mental health problems (SMHP). Despite this, there is a lack of treatments adapted for this group of clients. This qualitative study describes the development of a new intervention, guided by the principles of action research, for people with SMHP and MID/BIF and mental health professionals to help them talk about all aspects of the process of recovery. The intervention was developed in four cycles and in close cooperation with mental health professionals, experts by experience, other experts in the field of SMHP or MID/BIF, and clients. During all cycles there was a strong focus on the content of the intervention, exercises, understandable language, and drawings for visual support. This resulted in the intervention "Routes to Recovery", which covers both complaints and strengths, coping strategies, helpful (social) activities, and how to determine future steps in a recovery plan. This is a first step in helping professionals and their clients with SMHP and MID/BIF to have a conversation about personal strengths and what the client needs to re cover. Future research should investigate the effects of this intervention.